The Effect of Level Farmers' Knowledge In Some Active Chemical Insecticides Resistance to Control Plutella Xylostella Scale Laboratory - Catur Hermanto; Rasiska Tarigan; Fatiani Manik (JERAMI : Indonesian Journal of Crop Science, 2019)
Pengaruh Tingkat Pengetahuan Petani Pada Resistensi Beberapa Bahan Aktif Insektisida Kimia Untuk Mengendalikan Ulat Plutella Xylostella Skala Laboratorium The Effect of Level Farmers' Knowledge In Some Active Chemical Insecticides Resistance to Control Plutella Xylostella Scale Laboratory Catur Hermanto, Rasiska Tarigan dan Fatiani Manik Balai Penelitian Tanaman Sayuran – Badan Penelitian dan Pengembangan Pertanian Jln Tangkuban Perahu No 517, Lembang, Bandung Barat 40391; e-mail: mirasiskatarigan@gmail.com ABSTRAK Petani dan pestisida merupakan dua sisi yang saling berkaitan dalam mengendalikan serangan hama penyakit tanaman dilapangan Penggunaan pestisida oleh petani semakin hari kian meningkat khususnya didataran tinggi, namun peningkatan ini tidak diimbangi dengan pemahaman dalam menggunakan pestisida. Penelitian ini bertujuan untuk mengetahui pengaruh tingkat pengetahuan dan resistensi insektisida yang digunakan petani kubis di kabupaten Karo. Penelitian dilaksanakan di laboratorium Kebun Percobaan Berastagi dengan ketinggian tempat 1.340 mdpl yang dilaksanakan dari bulan september sampai november 2015. Pelaksanaan dibagi 2(dua) tahap. Tahap Pertama mengumpulkan makalah melalui teknik diskusi kelompok petani dan pengencer dan wawancara menggunakan kuisioner. Total jumlah responden 10 orang per 4 kecamatana. Dari hasil kuisioner dipilih jenis insektisida yang sering digunakan petani untuk diuji kepekaan ulat plutella xylostella terhadap insektisida yang diuji pada skala dilaboratoium. Empat perlakuan dengan masing-masing terdiri atas 9 taraf konsentrasi menggunakan rancangan acak lengkap dan diulang 3 kali. Hasil penelitian menunjukkan petani kubis dikabupaten karo melakukan pencampuran fungi dan insektisida > 2jenis dengan frekwensi penyemprotan 2 x 1 minggum serta dosis yang digunakan tidak sesuai dengan KF yang dianjurkan. Nilai LC 50 insektisida kimia dari bahan aktif klorantranilipro, prefenofos, sipemetrin dan kloropinofos berturut-turut 1,87 ml, 1,5 ml, 1,5 ml dan 2 ml. Dan waktu Waktu yang dibutuhkan untuk mematikan 50 % plutella xylostella (LT 50) dari keempat insektisida kimia berbahan aktif klorantranilipro, prefenofos, sipemetrin dan Kloropinfos berturut-turut adalah 39.20, 19.43, 23.57 dan 30.15 jam Kata kunci : Pengetahuan, Resistensi, Insektisida Kimia, Plutella xylostella , Laboratorium ABSTRACT. The Farmers and pesticides are important aspects that interrelated tocontroll pests in the field of plant diseases as well as opportunities occur resistensi. The use of pesticides by farmers is constantly increasing, especially in the highlands, but this increase is not offset by an understanding in the use of pesticides. The aimed of the research to find the knowledge and the use of insecticide resistance cabbage farmers in Karo District. The research was conducted at the laboratory of Berastagi experimental farm with altitude of 1,340 meters above sea level implemented from the month of September to November 2015. The implementation of divided by 2 (two) stages. The first is to collect issues by discussion technique of farmers group and diluent and interview using a questionnaire. Total number of respondents is ten peoples each four districts. From the questionnaire result so the selected types of insecticides often used by famers for the testing of sensitivity plutella xylostella to insecticides test at laboratory scale with four treatment. each consisting of 9 degree of concentration using a completely randomized design and repeated 3 times. each consisting of 9 degree of concentration using a completely randomized design and repeated 3 times. The results showed cabbage farmers in the county karo mixing fungi and insecticides> 2 types with spraying frequency of 2 x 1 week as well as the doses used did not correspond to the recommended KF. LC 50 value of the chemical insecticide active ingredient klorantranilipro, prefenofos, sipemetrin and kloropinofos successively 1.87 ml, 1.5 ml, 1.5 ml and 2 ml. Time and time required to shut down 50% of Plutella xylostella (LT 50) of the four chemical insecticide active ingredient klorantranilipro, prefenofos, sipemetrin and Kloropinfos are respectively 39.20, 19:43, 23:57 and 30.15 hours